Evaluating dimensions of destination image for selection of ecotourism destination in Bangladesh - Rahman, Mohammad Moshiur; Haque, A. K. M. Ahasanul; Suib, Fatin Husna (Southern Academic Publisher, 2022)
The rising image issues for destinations have become an escalating concern for ecotourism expansion in Bangladesh. The initial research about the destination image offered specific unknown gaps concerned with several advantages. However, this study aims to investigate the effect of destination image on ecotourism destination selection in Bangladesh. The data were collected by a self-administered questionnaire survey of 352 tourists and refined using structural equation analysis. SPSS-AMOS analyses revealed the existence of significant relationships between the variables. The findings demonstrate that a proper image would entice tourists to travel to Bangladesh’s ecotourism destinations. In addition, it may benefit Bangladesh tourism organizations by implementing plans to deal with sustainable development. Nevertheless, this study evaluates the destination image with a three-way interaction between ecotourism destination selection, which might serve as a precedent for future research.